Transmission Procedure of Kelong Jaga as an Oral Tradition of Kajang - Asmanur, A. Tenrinia; Meldawati, Sri Fatta; Mulyani, Andi; J, Rahmat; Winarti S, Indri (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
Maintaining the sustainability of oral culture is a necessity amidst the onslaught of the modern era that threatens its survival. This research focuses on investigating how the Kajang indigenious people maintain and continue to perform kelong jaga only through word of mouth as in Yugoslavia (Lord, 1981). The author analyzed the data using a descriptive qualitative approach. Performance recordings and interviews with experienced performers, traditional rulers, and locals comprised the data. The result shows 3 phases. This begins at an early age by listening and absorbing to the kelong jaga to be familiar with the words, tempo, sound, and so on; then next phase is practicing, learners practice the kelong jaga during their leisure time. They would usually gather in a little shelter in the middle of a rice field to act out kelong jaga; and the last phase is performing in front of real audience.